2015
DOI: 10.1136/jnnp-2014-310008
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity for NT5c1A antibody in sporadic inclusion body myositis predicts more severe motor, bulbar and respiratory involvement

Abstract: Objectives To explore phenotypic differences between individuals with sporadic inclusion body myositis (sIBM) who are seropositive for the NT5c1A antibody compared with those who are seronegative. Methods Cross-sectional clinical, serological and functional analysis in 25 consecutive participants with sIBM. Results All participants met criteria for clinically defined or probable sIBM. 18 of 25 participants with sIBM (72%) were seropositive for the NT5c1A antibody. No differences between median age and dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 40 publications
8
88
4
1
Order By: Relevance
“…So far, only one study has provided data indicating that anti-cN-1A seropositivity may be associated with a more aggressive form of IBM, including more prominent motor, bulbar and respiratory involvement [37]. …”
Section: Discussionmentioning
confidence: 99%
“…So far, only one study has provided data indicating that anti-cN-1A seropositivity may be associated with a more aggressive form of IBM, including more prominent motor, bulbar and respiratory involvement [37]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, the presence of the anti-NT5C1A autoantibody is associated with fewer rimmed vacuoles, highlighting the correlation with specific myopathological features [45][46][47][48][49][50]. In addition, the presence of the antibody also predicts more severe motor, bulbar and respiratory involvement [51]. Additional autoantibodies have been recently discovered, and their frequency and relevance remain to be defined [52][53][54][55].…”
Section: Why Study Autoantibodies In Myositis?mentioning
confidence: 99%
“…The presence of anti‐cN1A autoantibodies also suggests an immunological pathomechanism for sIBM. With regard to the clinicopathological features of sIBM patients with anti‐cN1A autoantibodies, an initial study suggested that seropositivity for the anti‐cN1A autoantibodies was associated with greater motor and functional disability: sIBM patients with the autoantibodies showed more prominent bulbar, facial and respiratory symptoms . In our investigation, the percentage of patients with hepatitis C virus antibodies was significantly lower, and the mean area of type 2 myofibers was significantly smaller in the anti‐cN1A‐positive group compared with the autoantibody‐negative group .…”
Section: Pathogenesis In Sibmmentioning
confidence: 45%
“…Furthermore, Greenberg reported that combination assays for all autoantibody isotypes (immunoglobulin [Ig]G, IgM and IgA) improved the diagnostic sensitivity for sIBM up to 76% . Since the identification of the presence of anti‐cN1A autoantibodies in sIBM, different methodologies for their detection have emerged, such as immunoprecipitation, immunoblotting with human skeletal muscle extracts or lysates of cN1A‐expressing human embryonic kidney 293 cells, and enzyme‐linked immunosorbent assays with recombinant full‐length cN1A protein or synthetic peptides derived from cN1A . In Table , we summarized the frequencies of seropositivity for anti‐cN1A autoantibodies in various diseases using different methodologies.…”
Section: Diagnosismentioning
confidence: 99%